Tapping irrigation potential: Exploring challenges and solutions in Western Nepal - Gurung, Pabitra; Shrestha, Nirman; Bhatta, Dinesh; Gnawali, Kapil; Upadhyaya, Bala Ram; Nepal, Santosh (CGIAR System Organization, 2023)
Irrigating farmland in Nepal increases crop yields, helping to reduce the country’s trade gap for agricultural commodities, and build a more food-secure economy. But despite having plenty of water available – 225 billion cubic meters each year – Nepal has a long way to go in tapping its resources to the full.